2001
DOI: 10.1097/00008571-200103000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of the human CYP3A locus: identification of a new, inducible CYP3A gene

Abstract: Proteins encoded by the human CYP3A genes metabolize every second drug currently in use. The activity of CYP3A gene products in the general population is highly variable and may affect the efficacy and safety of drugs metabolized by these enzymes. The mechanisms underlying this variability are poorly understood, but they include gene induction, protein inhibition and unknown genetic polymorphisms. To better understand the regulation of CYP3A expression and to provide a basis for a screen of genetic polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(151 citation statements)
references
References 33 publications
2
145
0
4
Order By: Relevance
“…The CYP3A5 gene is part of a cluster of cytochrome P450 genes on chromosome 7q21.1. 8 Cytochrome P450 proteins are monooxygenases that have an important role in the metabolism of both endogenous substances (for example, hormones) and exogenous substances (for example, drugs). 9,10 Cytochrome P450 proteins are expressed in an organ-specific manner, with CYP3A5 predominantly expressed in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The CYP3A5 gene is part of a cluster of cytochrome P450 genes on chromosome 7q21.1. 8 Cytochrome P450 proteins are monooxygenases that have an important role in the metabolism of both endogenous substances (for example, hormones) and exogenous substances (for example, drugs). 9,10 Cytochrome P450 proteins are expressed in an organ-specific manner, with CYP3A5 predominantly expressed in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…1 CYP3A consists of four genes, CYP3A4, CYP3A43, CYP3A5 and CYP3A7, located on 7q21-7q22.1. 2 The CYP3A5 gene is the major class representing about 50% of the hepatic CYP3A content, and is also highly expressed in the kidney. 3,4 An extreme interindividual and interethnic variability for the expression of CYP3A5 has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is plausible, because it has been shown that CYP3A43 is expressed in tissues related to steroid hormone synthesis and metabolism, and moreover in hormone related cancers, including carcinoma of the breast. [17][18][19] Thus, our finding of an association between the CYP3A43_74_delA polymorphism and poorly differentiated breast tumors adds a new candidate to the list of modulators of hormone-driven tumors. This should draw attention to CYP3A43 as a potential candidate marker for breast cancer prognosis.…”
Section: Discussionmentioning
confidence: 71%